Budget Budget Implementation and Accountability in Delta & Edo Public Service - Joel Bisina; Omamuyovwi Goodluck Afonughe (ARISTO, 2027)
Budget implementation and accountability remain persistent challenges in Delta and Edo local government public services, with far-reaching implications for governance quality, service delivery, and public trust in state institutions. This study examines the key factors, constraints, and institutional processes shaping how public budgets are executed in states. Although the budgeting framework is designed to align national priorities with available resources, actual implementation often diverges from approved plans. This disconnect is largely attributed to administrative delays, political interference, weak monitoring mechanisms, and volatility in government revenues. Together, these issues undermine fiscal discipline and sustain long-standing development shortfalls. Over time, several accountability mechanisms, including legislative oversight, audits, procurement regulations, and public financial management reforms, have been introduced to improve transparency and curb misuse of public funds.  The study identified several other modern challenges in budget implementation and accountability in Delta and Edo state public service as rooted in deep-seated structural problems such as weak institutional capacity, poor inter-agency coordination, inadequate sanctions for violations, and minimal citizen participation. These gaps reduce meaningful oversight and weaken efforts to ensure that public spending delivers tangible development outcomes. The study further highlights how late approvals, unpredictable cash releases, and budget and expenditures outside approved allocations erode policy credibility and disrupt project execution. Corruption and patronage networks also contribute to resource leakages, diminishing the value of public investments. Despite these challenges, ongoing reforms such as digital financial systems, medium-term expenditure frameworks, and open government initiatives offer cautious optimism. Sustaining progress in Delta and Edo public services at the local government level will depend on strong political will, continuous capacity building, and a deeply rooted culture of accountability. The study recommends that ultimately, improving budget implementation in Delta and Edo public services at the local government level requires a comprehensive approach centered on institutional strengthening and transparency building, and an immersed rooted culture of accountability.  Future research could expand on these findings by exploring broader perspectives and methodological approaches. Keywords: Budget; Accountability; Implementation; Civil Service;